2018
DOI: 10.1007/s13197-018-3230-y
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Listeria monocytogenes on the seafood contact surfaces of Tuticorin Coast of India

Abstract: was screened from different seafood contact surfaces in five sampling sites of fishing harbour, fish landing centers, seafood processing plants, fish market, and fish curing yards of Tuticorin Coast of India. 115 swab samples were collected and tested for the occurrence of by conventional and molecular methods. Overall, 5.22% of swab samples collected were positive for. The fishing harbour had high incidence (10.3%) of followed by fish landing centers (5.9%), and seafood processing plants (4.1%). Boat deck, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…There are numerous works that studied contamination routes or ecology and physiology of Listeria monocytogenes in a great range of food products. Seafood and aquatic products, fresh produce, milk, meat, cheese are some food types already examined (Castro et al, 2018;Honjoh et al, 2018;Selvaganapathi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous works that studied contamination routes or ecology and physiology of Listeria monocytogenes in a great range of food products. Seafood and aquatic products, fresh produce, milk, meat, cheese are some food types already examined (Castro et al, 2018;Honjoh et al, 2018;Selvaganapathi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…and L. monocytogenes were isolated from 24.34% and 8.69% of 115 seafood samples (Parihar A study conducted in Kerala's tropical seafood and fishery environment samples revealed L. innocua and L. monocytogenes (Das et al, 2013). Listeria monocytogenes could be detected from fishing harbours (10.30%), fish landing centres (5.90%), and seafood processing plants (4.10%) from Tuticorin Coast of India (Selvaganapathi et al, 2018). Listeria innocua (17.20%) and L. monocytogenes (2.70%) were isolated from the seafoods, RTE, and ready-to-cook (RTC) fish products from the retail fish markets of Kerala (Basha et al, 2019).…”
Section: Presence Of Listeria In Clinical Settings and Animalsmentioning
confidence: 99%
“…It has been well documented that infection of L. monocytogenes is derived from the consumption of contaminated food, such as ready-to-eat meat, soft cheese, and unpasteurized milk. Pathogenic marine bacteria-contaminated seafood was a threat to human health, particularly in coastal cities (10,11). Water and soil are also sources of L. monocytogenes infection (12).…”
Section: Introductionmentioning
confidence: 99%